Mind-Body Dualism in the Philosophy of Descartes: A Study of the Origins of the Mind-Body Problem - Fazio, Samuel Dominic (My University, 1977)
Prior to proposing a solution, it is necessary to first understand the problem which one is attempting to resolve. Many have wrestled to overcome the mind-body dualism of Rene Descartes' but few have made the effort to comprehend the factors which necessitated the Cartesian divorce between mind and body. To this latter task will I apply myself and this I propose to achieve by conducting an investigation for the main-spring which sets the Cartesian clock-work in motion.
If there is one central fact in the genesis of Descartes' thought, it must be his rationalism, his inherent trust in the process of reason as the guiding light in the search after truth. I will here conduct an examination of "reason" as it is unfolded in the Rules, which as a doctrine expounds Descartes' methodological approach to knowledge. I will then expand on the centrality of the Method and of reason, for Method is but an illustration of reason at work, by designating its importance as the foundation upon which Descartes' philosophy is built.
Having secured this general conclusion, I will then turn, in my final chapter, to my main theme: the mind-body problem, and here argue that Cartesian dualism, like the philosophy in general, is grounded in Descartes' rational attempt to gain knowledge. Finally, it will be concluded that Descartes' concept of matter, of "body" as extension, a concept grounded in reason itself, is the very feature which leads to the formulation of the dualism of mind and body.
Keywords: Philosophy; Philosophy